Synthesis and curing of new liquid crystalline epoxy monomers - Mossety-Leszczak, B.; Galina, H.; Włodarska, M. (Polimery, 2022)
On the basis of literature data, the structures, types and properties of liquid crystalline polymers have been characterized. The subject of the own research was two-step synthesis of four new liquid crystalline epoxy monomers. They were obtained by esterification of four various diphenols, showing rigid structure, with 4-pentenoic acid and subsequent epoxidation of obtained unsaturated esters using m- chloroperbenzoic acid (Scheme A). The structures of the cured products obtained as well as the courses of the monomers' curing were investigated using DCS, WAXS and polarization microscopy methods. The results concerning the curing of p- phenylene bis[4-(4,5-epoxypentanoyloxy)benzoatel (MU2 according to Scheme A) with p-phenylene diamine (PDA), 4,4'- diaminodiphenylmethane (DDM) and 4,4'-oxyphenylenediamine (DDE) (Figs. 3-6 and 8) were described in details. It was found that as a result of the process of mesogenic diepoxy monomers' curing carried out at the temperature of mesophase existence, liquid crystalline order had been mostly maintained.